2008
DOI: 10.1271/bbb.70796
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Amine Acceptor Protein Substrate Candidates of Transglutaminase in Rat Liver Extract: Use of 5-(Biotinamido) Pentylamine as a Probe

Abstract: Transglutaminases (TGs) are a family of enzymes that catalyze Ca 2þ -dependent post-translational modification of proteins by introducing protein-protein crosslinks (between specific glutamine and lysine residues), amine incorporation, and site-specific deamidation. In this study, new amine acceptor protein substrates of TG were isolated from rat liver extract and identified using 5-(biotinamido) pentylamine, a biotinylated primary amine substrate, as a probe. TG protein substrate candidates labeled with bioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…38 In this connection it is relevant to note that five TG2 candidate protein substrates (i.e.,: arginase-1, fructose-1,6-bisphosphatase, betaina-homocysteine S-methyltransferase BHMT, glyceraldehyde-3-phosphate dehydrogenase and glutathione S-transferase) have been shown to be enriched on the autophagosomal membrane. 39,40 In particular, a BHMT fragment has been shown to accumulate in the autolysosome fraction obtained from rat hepatocytes treated with inhibitors of intralysosomal protein degradation, similar to what we observed in this study for ANT-1 (Fig. 8A).…”
Section: Resultssupporting
confidence: 87%
“…38 In this connection it is relevant to note that five TG2 candidate protein substrates (i.e.,: arginase-1, fructose-1,6-bisphosphatase, betaina-homocysteine S-methyltransferase BHMT, glyceraldehyde-3-phosphate dehydrogenase and glutathione S-transferase) have been shown to be enriched on the autophagosomal membrane. 39,40 In particular, a BHMT fragment has been shown to accumulate in the autolysosome fraction obtained from rat hepatocytes treated with inhibitors of intralysosomal protein degradation, similar to what we observed in this study for ANT-1 (Fig. 8A).…”
Section: Resultssupporting
confidence: 87%
“…In many articles in research on the enzymes, lower molecular weight substrate molecules such as labeled primary amine (biotinylated pentylamine as glutamine-acceptor substrate) and Gln-containing peptide (as lysine-acceptor substrate) have been commonly used for the identification of possible protein substrates as well as in vitro detection of enzymatic activity15163536. Because the identified substrate candidates by this procedure appeared mostly crosslinked components in vivo , we believe the identified molecules in this study are highly possible as substrates by our identified substrate peptide.…”
Section: Discussionmentioning
confidence: 99%
“…BHMT interaction targets listed in the IntAct and BioGRID databases, as well as in the literature include approximately 22 interaction partners ( Table 9 ) [ 12 , 33 36 , 50 57 ]. However, only seven of these targets have been also identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Datasets derived from several high-throughput studies focused on the identification of protein targets for certain PTMs or on the elucidation of the human interactome have rendered data concerning BHMT. For example, phosphorylation [ 26 , 27 ], ubiquitination [ 28 ], acetylation [ 29 , 30 ], succinylation [ 30 ], carbonylation [ 31 ], and nitrosylation [ 32 ] are some of the PTMs detected on BHMT in these analyses, whereas other studies also identify BHMT as a target for modification by transglutaminase [ 33 ]. Nevertheless, in many cases the existence of these PTMs has not been verified by additional methods, neither the enzymes catalyzing these modifications have been identified.…”
Section: Introductionmentioning
confidence: 99%